Noise Reduction and Control in Hospital Environment: Design of the NeoNoise Project - Alberto Alves Carvalhais, Carlos (2019)
The “NeoNoise Project: Integrated Approach to Minimize Sound Pressure Levels in Neonatal Intensive Care Units” is being conducted by the Research Group on Occupational and Environmental Health of the Research Center on Health and Environment in neonatal intensive care units, since exposure to sound pressure levels in these spaces has been recognized as a factor that influences the quality and well‐being of the occupants (workers and others), as well as the recovery of premature infants who are hospitalized. This work reports the rationale and the design of the NeoNoise project as well as the methods used for data collection. A brief review on the results published and available for the scientific community is also made. In general, NeoNoise project intends to make an integration of all relevant factors, with the intention of presenting a guiding document to change the working practices and occupant's behaviors. So far, this study provided data on sound pressure levels by objective and subjective approaches, as well as information about the exposure factors and sensitivity of the occupants to noise.